Labor in the time of Trump - Kerrissey, Jasmine, 1977-; Weinbaum, Alys Eve, 1967-; Hammonds, Clare; Juravich, Tom; Clawson, Dan (ILR Press, an imprint of Cornell University Press, 2019)
"The labor movement has been under attack for decades; by understanding the nature of the right-wing attack, activists and scholars can analyze ways to build a working-class movement in the United States"--